Reliability Evaluation of Kumpai Feeder Distribution System at PT. PLN (Persero) ULP Siantan - Kurniawan, Ari Kurniawan; Fitriah, Fitriah; Arsyad, M. Iqbal (Faculty of Engineering, Universitas Tanjungpura, 2021)
The research on reliability index of a feeder aims to evaluate the reliability level of a feeder using the Reliability Index Assessment (RIA) method. This method evaluates the reliability of a 20 kV distribution network by calculating the reliability indexes of each load point. The evaluation results show the reliability index value per section of the Kumpai Feeder at PT. PLN (Persero) ULP Siantan within one year. The SAIFI values are 0.0092; 0.0012; 12,477; 0.0596; 0.0204; 0.0470; 0.0155; 0.0728, the SAIDI values are 0.0277; 0.0042; 37,746; 0.1862; 0.0741; 0.1524; 0.0493; 0.2209, the CAIDI values are 3.0108; 3.5; 3,025; 3.1241; 3.6323; 3.2425; 3.1806; 3.0343, the MAIFI values are 0; 5,480; 0.2145; 0.0020; 0.0038; 0.0042; 0.0006; 0.0014. The calculation results show that the 20 kV distribution system at PT. PLN (Persero) ULP Siantan at the Kumpai Feeder can be categorized as unreliable. Because the SAIFI value of this feeder exceeds the standard set by PT. PLN (Persero) which are 12.477 times/customer/year and 3.2 times/customer/year, respectively. The factors affecting the reliability index of the Kumpai feeder are the number and duration of blackouts, the number of customers, and the length of the distribution system channel.